Zetasizer measurements of copolymer-drug carrier system: poly (maleic anhydrite-co-vinyl acetate) -acriflavine conjugate - Dasdan, D. Sakar; Dizdar, A.; Karakus, G. (BULGARIAN ACAD SCIENCE, 2017)
Copolymeric drug carrier system, poly (maleic anhydrite-co-vinyl acetate) copolymer (MAVA) carrying acriflavine drug (AF) has been examined by Zeta Potential Analyzer to determine the stability and controlled drug release tests in water with different pHs and simulated body fluids. Zetasizer measurements such as zeta potential, mobility, and particle size of prepared copolymer, drug and copolymer-drug conjugate (MAVA-AF) were done. The activity of copolymer-drug conjugate in different pHs and simulated body fluids was checked via UV-VIS spectrophotometer as a function of time.
Keywords: copolymer-drug conjugate; stability; particle size; zeta potential; WATER-SOLUBLE POLYMERS; DELIVERY; Chemistry